Pembelajaran Al-Qur’an dengan Metode Ijmaly Untuk Anak Usia Dini - Nurhayati, Eti (ACIECE, 2017)
There are many methods of learning the Qur'an for an early childhood that has been known andimplemented in society, among other methods: Baghdady, Lamma, Barqy, Iqra, Uktub, Qira'aty,Tilawaty, Integrated Iqra, Classical Iqra, Dirosah, and others. This paper intends to offer themethod "ijmaly" as an alternative method, which is different from the existing method. Thestudy of the Qur'an by the method of ijmali is introduced to the children that starting from thesentence/verse as a whole and then specified in order to recognize the letter, not spelled, it ismore efficient because it is sufficient only to be introduced by three letters which arerepresentative of 28 letters of hijaiyyah, then given enrichment exercises with examples ofmeaningful sentences from Arabic or al-Qur'an that containing the letters that have beenintroduced, both single letters and words to strengthen and improve reading ability.